STOCHASTIC MODELING OF THE PROCESSES OF THE SALE BY MEANS OF COMPLEX POISSON FLOW - Y.A. LUKONIN; A.Y. LUKONIN (Advanced Engineering Research)
The casual processes of the sale are considered as casual Poisson flow of the all-stock deals, sizes which also are a random quantity. It is shown that if the known distribution of probability of the sizes of the deals and density of the flow of the buyers, that possible calculate distribution of probability of the sizes of the sale. There are laid down conditions, under which this sharing the sale will not be normal. Cite an instance distribution in real process of the sale, which are differ from Gauss distribution.